Pengembangan aplikasi android ‘EDD-N’ untuk deteksi dini penyakit neonatus: Sebuah Penelitian dan Pengembangan - Magfirah, Magfirah; Idwar, Idwar; Anita, Anita; Rahmli, Nurlaili; Veri, Nora (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Early detection of neonatal diseases can be done at home to prevent disease, reduce the burden of treatment, and reduce the risk of death. Neonates are susceptible to infection, so an application is needed to easily and quickly recognize the early symptoms of disease. This research does not support the local language, making it difficult for some mothers who are accustomed to using the local language.Method: The Research and Development (R&D) study design resulted in the development of an Android-based prototype application titled “Early Detection of Neonatal Diseases” (EDD-N). The steps in creating the application included: Focus Group Discussion (FGD), application concept design, development of the EDD-N application in collaboration with PT Bumantara Transformasi Digital, and feasibility testing. The research was conducted in Langsa City, Aceh Province, from June 3 to August 30, 2023. The number of respondents for each FGD and feasibility testing was 15 and 40 respondents, respectively. Feasibility testing used a Likert scale questionnaire with analysis in two stages.Results: The “Early Detection of Neonatal Diseases” (EDD-N) Android-based application consists of a main page titled “My Baby.” The application includes the health history of the mother and child, disease education comprising definitions, signs, and symptoms, and disease management. The content is presented in the form of images, videos, and narratives. Early detection is conducted via a questionnaire. The app's users include the general public, community health workers, healthcare professionals, and IT personnel. Users are rewarded with certificates, and the app's closing screen displays a logout menu. The usability test results for the EDD-N Android app from stage 1 to stage 2 yielded a value of 1.9. The p-value was 0,0001. The change in the EDD-N app process from stage 1 to stage 2 was 1.7. P-value 0,0001 (<0,05).Conclusion: The EDD-N app can be used for early detection of neonatal diseases.